Persons injured in the 2011 terror attacks in Norway - Relationship between post-traumatic stress symptoms, emotional distress, fatigue, sleep, and pain outcomes, and medical and psychosocial factors. Issue 22 (22nd October 2020) - Løvstad, Marianne; Månum, Grethe; Wisløff-Aase, Kristin; Hafstad, Gertrud Sofie; Ræder, Johan; Larsen, Ingar; Stanghelle, Johan Kvalvik; Schanke, Anne-Kristine
Abstract: Purpose: The main aim was to assess long-term post-traumatic stress symptoms, emotional distress, fatigue, sleep disturbances and pain in individuals hospitalized with physical injuries after two terror attacks in Oslo in 2011, approximately three years after the events. A secondary aim was to explore the relationship between these outcomes and medical and psychosocial factors. Materials and methods: Thirty of 43 potential persons participated. Injury characteristics were collected from medical charts. Level of post-traumatic stress, emotional distress, fatigue, sleep disturbances and pain was assessed and the association with injury severity, resilience, optimism, neuroticism and extroversion, and perceived access to social support was explored. Results: Nine of 30 met criteria for full or partial PTSD, and 14 of 30 displayed clinical levels of emotional distress. Fifteen reported moderate to severe fatigue, and 16 said sleep disturbances affected their daily life. Twelve indicated that pain affected daily activities and work ability, and 15 that pain affected their quality of life. I Resilience, optimism, neuroticism, and perceived social support, were associated with outcomes, but injury severity was not. When controlling for pain, many of the psychosocial variables failed to reach significance. Conclusions: Injury severity was not associated with outcomes. On the other hand, psychosocial factors were, but seemed to be influenced by pain. Implications for rehabilitation: Persons who have obtained physical injuries under extreme psychological conditions such as terror, are at high risk of poor long-term outcomes, and will often be in need of comprehensive interdisciplinary rehabilitation services. Psychological outcomes are not associated with severity of physical injury, but premorbid and current psychological variables such as resilience, optimism, personality, and access to social support are highly associated with long-term outcome. Longstanding pain seems to diminish or weaken the role of protective psychological factors and should be addressed in the rehabilitation context.